2016
DOI: 10.4142/jvs.2016.17.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Canine adipose tissue-derived mesenchymal stem cells ameliorate severe acute pancreatitis by regulating T cells in rats

Abstract: Severe acute pancreatitis (SAP) is associated with systemic complications and high mortality rate in dogs. Mesenchymal stem cells (MSCs) have been investigated for their therapeutic potential in several inflammation models. In the present study, the effects of canine adipose tissue-derived (cAT)-MSCs in a rat model of SAP induced by retrograde injection of 3% sodium taurocholate solution into the pancreatic duct were investigated. cAT-MSCs labeled with dioctadecyl-3,3,3′-tetramethylindo-carbocyanine perchlorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…As shown in acute pancreatitis models, 16,29,[39][40][41] we also found that the protective effects of MSC therapy were multifactorial and targeted several cell types in the pancreas. First, ASCs protected pancreatic cells from ethanol-and cerulean-induced cell death.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As shown in acute pancreatitis models, 16,29,[39][40][41] we also found that the protective effects of MSC therapy were multifactorial and targeted several cell types in the pancreas. First, ASCs protected pancreatic cells from ethanol-and cerulean-induced cell death.…”
Section: Discussionsupporting
confidence: 66%
“…14 Compared with MSCs from other tissues, ASCs display greater regenerative capacity based on their differentiation and paracrine activities. 15 The protective effects of ASCs have been shown in rodent models of severe acute pancreatitis, 16 type 1 diabetes, 17,18 experimental autoimmune encephalomyelitis, 19 rheumatoid arthritis, systemic lupus erythematosus, and other disorders. 20,21 ASCs are currently being tested in clinical trials for the treatment of Crohn'srelated rectovaginal fistula, 22 refractory rheumatoid arthritis, 23 severe osteoarthritis of the knee, 24 systemic sclerosis, 25 and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the transplantation of adipose-derived mesenchymal stem cells (aScs) markedly improves revascularization and tissue perfusion in limb ischemia (17). Various studies have demonstrated that aScs have a treatment effect for severe acute pancreatitis (AP) (18), type 1 diabetes (19,20) and experimental colitis (21) in animal models. aScs are currently being tested in clinical trials for the treatment of transsphincteric cryptoglandular fistulas (22), crohn's-related rectovaginal fistula (23), refractory rheumatoid arthritis (24), severe osteoarthritis of the knee (25), systemic sclerosis (26) and other diseases (27).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cell (MSC) therapies are emerging as potential adjunct or single‐agent treatments for a variety of inflammatory and immune‐mediated conditions in veterinary medicine, including osteoarthritis, tendonopathy, spinal cord trauma, keratoconjunctivitis sicca, pancreatitis, inflammatory bowel disease (IBD), and feline gingivostomatitis . In these applications, stem cells are used for their autocrine and paracrine immunomodulatory effects . Adipose‐derived MSC (AD‐MSC) have gained in popularity because of the abundance and ease of harvesting adipose tissue, documented multipotency of the cells, greater self‐renewal capacity, and superior MSC:volume ratio compared to bone marrow‐derived MSC …”
Section: Introductionmentioning
confidence: 99%